The precipitative effects of pandemic on open innovation of SMEs: A scientometrics and systematic review of industry 4.0 and industry 5.0 - Meena Madhavan; Sutee Wangtueai; Mohammed Ali Sharafuddin; Thanapong Chaichana (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This research aims to study the pre-pandemic and pandemic-period Industry 4.0 and Industry 5.0 characteristics in SME research using scientometrics and systematic review using the PRISMA 2020 approach. A total of 691 articles were found in SCOPUS database using keywords (("Industry 4.0" OR "Industry 5.0") AND "SME"). However, 398 documents, which were either conference proceedings, reviews, book chapters or published in languages other than English, were excluded, and the remaining 221 articles that were published in SCOPUS indexed Journals were included in the study. This research adopted a novel mix of scientometrics and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 recommendations for identifying the thematic evolution of pre-pandemic and pandemic-period Industry 4.0 and Industry 5.0 SME Research. The major findings of this systematic review are, (1) There is a conceptual shift among researchers in studying the Industry 4.0 adoption of SMEs during the pandemic period; (2) The pandemic period research focused on (a) human-centric approaches, (b) adoption/acceptance models, (c) cost-effective solutions, (d) COVID-19 impact and resilience, (e) artificial intelligence and predictive maintenance, and (f) the emerging role of open innovation in Industry 4.0 adoption of SMEs; (3) Though the concept of Industry 5.0 clearly emerged and supplemented industry 4.0, the keyword "Industry 5.0" is not widely adopted by researchers. From the systematic literature review, a conceptual model for assessing the Industry 4.0 adoption and digital transformation of SMEs, digital integration of value chains and participation in a global value chain for trade expansion and sustainable growth of SMEs is proposed.
Keywords: 650; COVID-19; SMEs; industry 4.0; industry 5.0; pre-pandemic; PRISMA; systematic review